Dual role of the miR‐146 family in rhinovirus‐induced airway inflammation and allergic asthma exacerbation. Issue 6 (28th May 2021) - Laanesoo, Anet; Urgard, Egon; Periyasamy, Kapilraj; Laan, Martti; Bochkov, Yury A.; Aab, Alar; Magilnick, Nathaniel; Pooga, Margus; Gern, James E.; Johnston, Sebastian L.; Coquet, Jonathan M.; Boldin, Mark P.; et al.
Abstract: Rhinovirus (RV) infections are associated with asthma exacerbations. MicroRNA‐146a and microRNA‐146b (miR‐146a/b) are anti‐inflammatory miRNAs that suppress signaling through the nuclear factor kappa B (NF‐κB) pathway and inhibit pro‐inflammatory chemokine production in primary human bronchial epithelial cells (HBECs). In the current study, we aimed to explore whether miR‐146a/b could regulate cellular responses to RVs in HBECs and airways during RV‐induced asthma exacerbation. We demonstrated that expression of miR‐146a/b and pro‐inflammatory chemokines was increased in HBECs and mouse airways during RV infection. However, transfection with cell‐penetrating peptide (CPP)‐miR‐146a nanocomplexes before infection with RV significantly reduced the expression of the pro‐inflammatory chemokines CCL5, IL‐8 and CXCL1, increased interferon‐λ production, and attenuated infection with the green fluorescent protein (GFP)‐expressing RV‐A16 in HBECs. Concordantly, compared to wild‐type ( wt ) mice, Mir146a/b −/− mice exhibited more severe airway neutrophilia and increased T helper (Th)1 and Th17 cell infiltration in response to RV‐A1b infection and a stronger Th17 response with a less prominent Th2 response in house dust mite extract (HDM)‐induced allergic airway inflammation and RV‐induced exacerbation models. Interestingly, intranasal administration of CPP‐miR‐146a nanocomplexes reduced HDM‐induced allergic airway inflammation without a significant effect on the Th2/Th1/Th17 balance in wild ‐ type mice. In conclusion, the overexpression of miR‐146a has a strong anti‐inflammatory effect on RV infection in HBECs and a mouse model of allergic airway inflammation, while a lack of miR‐146a/b leads to attenuated type 2 cell responses in mouse models of allergic airway inflammation and RV‐induced exacerbation of allergic airway inflammation. Furthermore, our data indicate that the application of CPP‐miR‐146a nanocomplexes has therapeutic potential for targeting airway inflammation. Abstract : miR‐146a has anti‐inflammatory properties in human bronchial epithelial cells and mouse airways during rhinovirus infection and in case of allergic inflammation. Particular cell penetrating peptide(CPP)‐miR‐146a nanocomplexes have therapeutic potential for targeting of airway inflammation.